EMERGENCY REMOTE TEACHING OF MANDARIN CLASSES DURING THE COVID-19 PANDEMIC - Stephanie, Clarissa; Ginting, Daniel (Ma Chung Press, 2022)
During the pandemic, education is often called “emergency remote teaching.” Remote teaching and learning is a learning system that occurs beyond the physical buildings of the campus/school using the internet and electronic gadgets (computers, smartphones, etc.), which can help the teaching and learning process occur remotely. This paper employed a survey method to gather the data. With this method, the authors designed questions through an online questionnaire to tap teachers’ perceptions about how they have run online classes during the pandemic. This study focuses on two problem formulations: the extent to which Chinese language teachers carry out emergency Chinese online teaching and learning activities during the pandemic and how teachers carry out Chinese emergency online teaching and learning activities. This study found diversity in implementing Chinese emergency online classes, where most research subjects belong to high-prepared category. This proves that the response of Chinese language teachers is quite adaptive to implementing emergency online learning during this pandemic. Keywords: remote, online, independent, emergency